Balancing the redox reaction in acidic media:
As2O3(s) + NO3-(aq) → H3AsO4(aq) + N2O3
Step 1: Separate the whole reaction into two half-reactions:
As2O3 (s) → H3AsO4(aq) NO3– (aq) → N2O3 (aq)
Step 2: Balance the non-hydrogen and non-oxygen elements first:
As2O3 (s) → 2 H3AsO4(aq) 2 NO3– (aq) → N2O3 (aq)
Complete and balance the following equation:
As2O3(s) + NO3-(aq) → H3AsO4(aq) + N2O3(aq) (acidic solution)
Frequently Asked Questions
What scientific concept do you need to know in order to solve this problem?
Our tutors have indicated that to solve this problem you will need to apply the Balancing Redox Reaction concept. You can view video lessons to learn Balancing Redox Reaction. Or if you need more Balancing Redox Reaction practice, you can also practice Balancing Redox Reaction practice problems.